2021
DOI: 10.1021/acs.jpca.1c00183
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Gas-Phase Unimolecular Dissociation for Bond Dissociation Energies: Comparison of Statistical Rate Models within RRKM Theory

Abstract: The Rice-Ramsperger-Kassel-Marcus (RRKM) theory provides a simple yet powerful rate theory for calculating microcanonical rate constants. In particular, it has found widespread use in combination with gas-phase kinetic experiments of unimolecular dissociations to extract experimental bond dissociation energies (BDE). We have previously found several discrepancies between computed BDE values and the respective experimental ones, obtained with our empirical rate model, named L-CID. To investigate the reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…Treating the results in reverse order, threshold collision-induced dissociation (T-CID) of electrosprayed 4 , reported in our previous work, was clean in the mass spectrometer at the low energies included in the fit, producing only products of Pd–Cu bond cleavage. The fitting of the energy-resolved CID cross-section with L-CID accounts for, among other factors, the kinetic shift in the threshold by applying a version of statistical rate theory . Especially the treatment of the density-of-states function, ρ­( E ), for large molecules, large meaning up to some hundreds of atoms, requires approximations, which in the case of L-CID amounts to treating the ensemble of 3N-6 vibrational frequencies with a single “effective” frequency obtained as a fit parameter.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Treating the results in reverse order, threshold collision-induced dissociation (T-CID) of electrosprayed 4 , reported in our previous work, was clean in the mass spectrometer at the low energies included in the fit, producing only products of Pd–Cu bond cleavage. The fitting of the energy-resolved CID cross-section with L-CID accounts for, among other factors, the kinetic shift in the threshold by applying a version of statistical rate theory . Especially the treatment of the density-of-states function, ρ­( E ), for large molecules, large meaning up to some hundreds of atoms, requires approximations, which in the case of L-CID amounts to treating the ensemble of 3N-6 vibrational frequencies with a single “effective” frequency obtained as a fit parameter.…”
Section: Discussionmentioning
confidence: 58%
“…The fitting of the energy-resolved CID cross-section with L-CID 11 accounts for, among other factors, the kinetic shift 28 in the threshold by applying a version of statistical rate theory. 13 Especially the treatment of the densityof-states function, ρ(E), for large molecules, large meaning up to some hundreds of atoms, requires approximations, which in the case of L-CID amounts to treating the ensemble of 3N-6 vibrational frequencies with a single "effective" frequency obtained as a fit parameter. Testing and calibration of the approximation against a panel of reference molecules found that ρ(E) from a Beyer−Swinehart direct state count with explicit frequencies could be reliably reproduced by the effective frequency approximation over a range of over 100 kcal/mol in E, and 50 orders of magnitude in ρ(E).…”
Section: ■ Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Experimental errors are determined by the degree of reproducibility, as well as an error analysis of the L-CID model. [11] Unsaturated hydrocarbon E 0,exp. Upon treatment of [LAuCl] complexes containing different dialkylbiaryl phosphine-and NHC-ligands with the metalated (2-phenylethyl)dimethylamine nucleophile, obtained by the abovementioned method, we were pleased to observe that the transmetalation took place and that the desired 2-aminoalkyl gold complexes were formed.…”
Section: Synthesis Of 2-aminoalkylgold(i) Complexes and Their Reactiv...mentioning
confidence: 99%